UJI AKTIVITAS ANTI JAMUR EKSTRAK MINYAK ATSIRI KULIT JERUK CITRUS NOBILIS VAR.MICROCARPA TERHADAP PERTUMBUHAN JAMUR SCHIZOPHYLLUM COMMUNE FRIES - Pasaribu, Sri Muliati Hasnah; Wardenaar, Evy; dina, Wah (JURNAL HUTAN LESTARI, 2015)
The research objective was to determine the anti-fungal activity and the  effective concentration of essential oils from orange pericarp extract in inhibiting  Schizophyllum commune Fries growth.  Concentration of essential oils orange pericarp extracts used for the treatment were, 0%, 2%, 4%, 6%, 8% and 10 %. The  toxicity testing method PDA medium mixed with the essential oils orange pericarp extract. Mean while at concentration 2% the anti fungal activity was catagorized as weak, at concentration  4% was medium, at concentration 6% and 8% was strong and at concentration 10% was very strong respectively. Result of the research showed that concentration 10% was the strongest anti fungal activity which inhibited the growth of S.commune at 78,39%. Concentration 10% of orange pericarp essential oil extract an optimum concentration to inhibited S.commune fungus growth. Key word : Anti fungal, essential oils, orange pericarp, Schizophyllum commune Fries.